2017
DOI: 10.11609/jott.3358.9.6.10269-10285
|View full text |Cite
|
Sign up to set email alerts
|

<b>Identity of <I>Sphaerotheca pluvialis</I> (Jerdon, 1853) and other available names among the burrowing frogs (Anura: Dicroglossidae) of South Asia</b>

Abstract: Species diversity of South Asian burrowing frogs within the genus Sphaerotheca is still obscure because of lack of taxonomic review.  There are taxonomic issues within the genus Sphaerotheca with several names being synonymized to S. breviceps and names, such as S. pluvialis, being available without proper diagnosis. To resolve the taxonomic confusion, we describe and diagnose S. pluvialis by designating a neotype from Carnatic region of southern India, from where the original species was described, and make S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…While Sphaerotheca breviceps was thought to be widespread and has been recorded earlier from the Delhi region (Zoological Survey of India 1997), recent studies now show the presence of genetically cryptic species that were earlier included in the S. breviceps species complex. Dahanukar et al (2017) for instance, described S. pluvialis, a species that may earlier have been grouped with S. breviceps. Similarly, Padhye et al (2017) described the species S. pashchima (from western India) from specimens earlier identified as S. breviceps.…”
Section: Discussionmentioning
confidence: 99%
“…While Sphaerotheca breviceps was thought to be widespread and has been recorded earlier from the Delhi region (Zoological Survey of India 1997), recent studies now show the presence of genetically cryptic species that were earlier included in the S. breviceps species complex. Dahanukar et al (2017) for instance, described S. pluvialis, a species that may earlier have been grouped with S. breviceps. Similarly, Padhye et al (2017) described the species S. pashchima (from western India) from specimens earlier identified as S. breviceps.…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al (2019) raised doubt about possible speciation in populations of S. dobsonii from higher and lower elevations. The delimitation analysis clearly showed that the specimens mentioned by Dahanukar et al (2017) from all the locations in the states of Karnataka and Maharashtra are of the same species.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L Ementioning
confidence: 91%
“…Sequences generated in the current study were deposited in GenBank (accession numbers MT798138-MT798141 and MT773254-MT773262; Table 1). New sequences were added to the database used by Dahanukar et al (2017), , and Prasad et al (2019) for genetic analysis. Generated sequences were cleaned manually in MEGA 7 (Kumar et al 2016) using chromatograms visualized in Chromas V.2.6.5 (Technelysium PTY.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations